The impacts of Hevea brasiliensis (rubber tree) plantation on soil nutrients in Southern Nigeria - EMMANUEL OFUDJAYE NDAKARA; ODAFIVWOTU OHWO (Smujo International, 2022)
Abstract. Ndakara OE, Ohwo O. 2022. The impacts of Hevea brasiliensis (rubber tree) plantation on soil nutrients in Southern Nigeria. Nusantara Bioscience 14: 234-239. This study investigated how Hevea brasiliensis (Willd. ex A.Juss.) Müll.Arg. impact on the soils within the humid rainforest ecosystem of Nigeria. The study used quasi-experimental and stratified random sampling techniques to select sampling units. Samples of soils under H. brasiliensis and rainforest (the control) were collected using an auger, and their laboratory analyses for total organic matter (TOM), total nitrogen (N), available phosphorus (P), exchangeable potassium (K), and pH were carried out using standard methods. Data generated were statistically analyzed using the mean, standard deviation, standard error of mean, and t-test. Findings showed that the soils under rainforest have higher nutrient properties than plantations of H. brasiliensis. Soil pH values were lower under rainforest than under plantations of H. brasiliensis. While TOM, N, and K differed significantly between rainforest and H. brasiliensis at a 5% confidence level, available phosphorus and pH were insignificant at a 5% confidence level. Tree species' capability to improve soil nutrition reflects its positive impact on the ecosystem. Since soil nutrients under H. brasiliensis are lower than soil nutrients under rainforest, efficient application of organic manure is required to improve the soil nutrient status for sustainable ecosystem functioning and management of the degraded rainforest environment.